Hubungan Mekanisme Koping Individu dengan Kejadian Resiko Bunuh Diri pada Remaja di SMAN 1 Limboto - Firmawati Firmawati; Nur Uyuun Biahimo; Siti Rahmatia Husain (Malahayati Nursing Journal, 2025)
ABSTRACT Adolescents are known to have unstable emotions because they experience emotional changes that are at risk of increasing depression and resulting in suicidal ideation. Adapting to existing stressors can help adolescents prevent suicidal ideation and reduce the risk of suicidal behavior by increasing coping mechanisms to suppress suicidal ideation. The aim of this research is to analyze the relationship between individual coping mechanisms and the risk of suicide among adolescents at SMAN 1 Limboto. The research design uses quantitative correlational with cross sectional. Sampling used probability sampling with proportional stratified random sampling technique with a total of 88 respondents. Data collection uses a questionnaire sheet. Statistical analysis using chi square (x2) The results showed that the majority of teenagers' coping mechanisms were adaptive coping mechanisms, 57 people (64.8%) with a low risk of suicide, 50 people (56.8%), and the lowest were teenagers with maladaptive coping mechanisms with high risk. suicide was low at 1 person (1.1%) with statistics obtained by Asymp. sig (2 tailed) p value of 0.000 0.05, which means that there is a relationship between individual coping mechanisms and the risk of suicide among teenagers at SMAN 1 Limboto. The conclusion is that the better a teenager's coping mechanisms, the lower the level of suicide risk experienced by teenagers. Keywords: Coping Mechanisms, Suicide Risk, Adolescents  ABSTRAK Remaja dikenal mempunyai emosi yang tidak stabil karena mengalami perubahan emosional yang beresiko meningkatkan depresi hingga mengakibatkan timbulnya ide untuk bunuh diri. Beradaptasi dengan stressor yang ada dapat membantu remaja mencegah ide bunuh diri dan mengurangi resiko perilaku bunuh diri dengan cara meningkatkan mekanisme koping untuk menekan ide bunuh diri. Tujuan penelitian ini adalah untuk menganalisis Hubungan Mekanisme Koping Individu dengan Kejadian Resiko Bunuh Diri Pada Remaja Di SMAN 1 Limboto. Desain penelitian menggunakan kuantitatif korelasional dengan cross sectional. Pengambilan sampel menggunakan probability sampling dengan teknik propotional stratified random sampling dengan jumlah responden 88 orang. Pengumpulan data menggunakan lembar kuesioner. Analisa statistik menggunakan chi square (x2). Hasil penelitian menunjukkan mayoritas mekanisme koping remaja dengan mekanisme koping adaptif sejumlah 57 orang (64.8%) dengan resiko bunuh diri rendah sejumlah 50 orang (56.8%), dan yang terendah adalah remaja dengan mekanisme koping maladaptif dengan resiko bunuh diri rendah sejumlah 1 orang (1.1%) dengan statistik didapatkan Asymp. sig (2 tailed) p value sebesar 0.000 0.05 yang artinya bahwa terdapat hubungan mekanisme koping individu dengan kejadian resiko bunuh diri pada remaja di SMAN 1 Limboto. Kesimpulannya adalah semakin baik mekanisme koping remaja maka semakin rendah tingkat resiko bunuh diri yang dialami remaja. Kata Kunci: Mekanisme Koping, Resiko Bunuh Diri, Remaja